Military vaccines in today's environment - Connie S. Schmaljohn; Leonard A. Smith; Arthur M. Friedlander (Taylor & Francis Group, 2012)
The US military has a long and highly distinguished record of developing effective vaccines against pathogens that threaten the armed forces. Many of these vaccines have also been of significant benefit to civilian populations around the world. The current requirements for force protection include vaccines against endemic disease threats as well as against biological warfare or bioterrorism agents, to include novel or genetically engineered threats. The cost of vaccine development and the modern regulatory requirements for licensing vaccines have strained the ability of the program to maintain this broad mission. Without innovative vaccine technologies, streamlined regulatory strategies, and coordinating efforts for use in civilian populations where appropriate, the military vaccine development program is in jeopardy.